GAMBARAN IMPACT AND INFLUENCE SEORANG AYAH DI MATA ANAK (STUDI FENOMENOLOGIS SEORANG PEWARIS RUMAH MAKAN SIMPANG RAYA) - Yanladila Yeltas Putra; Zakwan Adri (Departemen Psikologi, Universitas Negeri Padang, 2025)
Preparing a successor for a business with branches throughout Indonesia is difficult. Moreover, the company has entered the 3rd generation. Of course, an heir must understand the traditions that have been built by his predecessors. This is also the case for the Heir of a famous Restaurant in Indonesia, namely Simpang Raya Restaurant. This study aims to obtain a broad and in-depth picture of how the dynamics of parents prepare the heir to Simpang Raya Restaurant, especially how they determine and choose the heir to their business, how they prepare their prospective heirs, which of course includes contributions to how they influence and persuade (Impact and Influence) prospective heirs so that Simpang Raya Restaurant can exist and even develop more in the future. This study uses a qualitative methodology with a phenomenological approach, namely how we understand experience and how subjects give meaning to their experiences. In this study, five major themes were found, namely, introducing business, supporting and understanding, discussing, basurau, and dilake'an.